EP017/#425 Comparison of NAPI2B expression from paired tissue samples in a clinical study of upifitamab rilsodotin (UPRI; XMT-1536) supports a strategy of testing in archive material. (4th December 2022) - Richardson, Debra; Barve, Minal; Saltos, Andreas; Papadopoulos, Kyriakos; Hays, John; Tolcher, Anthony; Ellard, Susan; Doroshow, Deborah; Mitchell, Paul; Zarwan, Corrine; Werner, Theresa; Anderson, Charles; et al.
Abstract : Objectives: UpRi is a first-in-class NaPi2b ADC with a novel scaffold-linker-payload that enables high drug-to-antibody ratio and controlled bystander effect. NaPi2b is a sodium-dependent phosphate transporter broadly expressed in high-grade serous ovarian cancer (HGSOC), with limited expression in normal tissues. Emerging UpRi data suggests a relationship between high NaPi2b expression and clinical activity. To determine if archive material would be sufficient to classify biomarker status, we evaluated NaPi2b expression in paired freshly biopsied and archive material from the Phase 1b study. Methods: Two sample sets were evaluated for NaPi2b expression using an IHC assay. The first set (18 pairs) was procured from tissue banks, representing synchronous sampling of primary and metastatic lesions to establish a reference NaPi2b heterogeneity rate. The second set were matched metachronous samples (56 pairs) from the Phase 1b study, sampled prior to UpRi administration. Expression was shown as a tumor proportion score (TPS ≥75). Concordance rates and Kappa values were calculated. Results: Synchronous primary and metastatic lesions from an archival tumor bank showed a concordance rate of 72%. When fresh biopsy samples from a clinical study cohort were compared to archival tissue from the same patient, 76% of NaPi2B high tumors in archival tissue were also high in fresh samples, regardless of the elapsed time between archival and fresh tissue samples. Conclusions: UpRi is being evaluated in clinical trials, requiring either fresh or archival tissue for NaPi2b expression assessment. The high expression concordance rate seen suggests that NaPi2b remains consistent throughout chemotherapy treatment, supporting use of archival tissue for analysis.